An evidence-based review of hyperbaric oxygen for children with cerebral palsy - F. M. Bischof (AOSIS, 2001)
This paper reviews the evidence in the literature for the use of hypebaric oxygen (HBO) in the treatment of cerebral palsy (CP). To date there are only two published studies on the outcome of HBO administration in CP. A pilot study showed significant improvement in gross motor function but provided a low level of evidence. A recent multicentre, double blind, placebo controlled trial reported similar improvements in both HBO and placebo groups, but no difference between the groups. This study had a high level of evidence. The results suggest that participation in the trial produced clinically important gains in function. The outcome of the study implies that HBO may have a placebo effect in CP.